The value and power of discipline - Abbott, Edmund Clarence (My University, 1893)
Introduction: The world discipline means to develop by instruction or exercise; or a state of sujection to rule and authority. While the word has many other shades of meaning, the two given definitions are the meanings with which this thesis deals. Human abilities and powers like most other things are not so highly developed that they can not be improved. The human being as it comes into this world is ignorant; but by observation and teaching the powers develop, the understanding unfolds until each individual stands before the world learned; equal with his associates, strengethened by the accumulated knowledge of the past together with is original efforts. The value of all discipline lies in his faculty of mankind to grow and develop in strength and intelligence with experience and teaching. As there are many forms of most everything so are there various forms of discipline.
Citation: Abbott, Edmund Clarence. The value and power of discipline. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Discipline; Human abilities; Powers; Experience; Teaching; Theses; Manuscripts (documents)